Aktivitas Enzim Protease dan Lipase Viscera Ikan Kembung (Restrelliger sp) pada pH Dan Konsentrasi Garam Berbeda - Bustari Hasan; Desmelati Desmelati; Dian Iriani; Titania Nugroho; M Andesba Arifin; Andhra Syatapahana (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
This research was conducted to measure the activity of visceral protease and lipase of mackerel (Rastrelligersp) at different pH and salt concentration. Mackerel, weighing ± 150 g/each were obtained from a fish market in Pekanbaru. Fish weretransported to the laboratory; and at the laboratory, the fish were eviscerated and their visceral organs (intestines, kidneys, liver, spleen, cord, pancreas and gonad) were blended in Tris-HCl buffer and filtered for their crude enzyme extract. The protease activity was measured at pH 6, 7, 8, 9, 10 and 11; and lipase activity was measured at pH2, 3, 4, 5, 5.5, 6, 7, 8, 9, 10 and 11. The protease and lipase activity werealso measured atsalt concentration 0%, 3%, 6%, 9%, 12% and 15%. The results showed that the protease and lipase activity varies with pH value and salt concentration. Protease activity at pH 11 (1,610µmol/ml)and salt concentration 6%(0,869 µmol/ml)showed the highest activity; and pH 10 (0,031µmol/ml) and salt concentration 15% (0,073µmol/ml) was the lowest activity. Lipase activity at pH 4 (2,428 µmol/ml) and salt concentration 3% (4,131µmol/ml) was the highest activity; and pH 11 (0,042µmol/ml) and salt concentration 15% (2,237µmol/ml) was the lowest activity. The protease and lipase activity were decreased withthe increasing of salt concentration.